Magnetic activated carbon loaded with tungsten oxide nanoparticles for aluminum removal from waters. Issue 3 (June 2017) - Saleh, Tawfik A.; Tuzen, Mustafa; Sarı, Ahmet
Highlights: Magnetic activated carbon was modified by tungsten oxide nanoparticles. The composite showed high efficiency for aluminim sorption from aqueous solution. The composite showed thermal stability, excellent recovery and reusability. Abstract: Magnetic activated carbon/tungsten nanocomposite (AC/Fe/W) was prepared as an environmentally friendly cost-effective adsorbent. Its chemical, morphological, thermal degradation and surface properties were characterized by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), energy dispersive X-ray (EDX), Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) and surface area (BET) techniques. The developed adsorbent was used for the remediation of Al(III) ions from aqueous solution. The optimum experimental conditions were found under response surface methodology (RSM) using central composite design (CCD). The adsorption efficiency was achieved up to 90% within 45 min at pH 5 at 24 °C. To investigate the suitability of the process, the equilibrium data were evaluated by Langmuir and Freundlich isotherm models. The adsorption capacity of AC/Fe/W composite was found to be 184.12 mg g −1 . The kinetic examinations showed that the pseudo-second order was the best fitting model to explain the adsorption mechanism. The activation energy of adsorption ( E a ) was determined as 2.04 kJ mol −1, indicating that the adsorption process was carried out via physical sorption mechanism. Thermodynamic findings indicated the exothermic and spontaneous nature of the adsorption process and increased randomness at the solid-solution interface. By using 1.0 mol L −1 HCl solution, the adsorbed Al(III) ions were desorbed at high effectiveness and also the composite can be reused up to five cycles. Based on all of the results, it can be concluded that the fabricated composite material is effective and promising adsorbent for the cleaning treatment of Al(III) ions from wastewaters by large-scale designed adsorption system.